P.172 Work-up and management of asymptomatic extracranial traumatic vertebral artery injury. (June 2022) - MacLean, MA; Touchette, CJ; Dude, T; Almojuela, A; Bergeron, D; Kameda-Smith, M; Persad, AR; Sader, N; Alant, J; Christie, SD
Abstract : Background: Extracranial traumatic vertebral artery injury (eTVAI) is common following non-penetrating head and neck trauma. Most cases are initially asymptomatic with an increased risk for stroke. Consensus is lacking regarding screening, treatment, and follow-up of asymptomatic patients with eTVAI. Our objective was to investigate national practice patterns reflecting these domains. Methods: An electronic survey was distributed via the Canadian Neurological Sciences Federation and Canadian Spine Society. Two case-based scenarios featured asymptomatic patients with eTVAI. Case 1: non-displaced cervical lateral mass fracture; angiography stratified by luminal diameter reduction. Case 2: complex C2 fracture; angiography featuring pseudoaneurysm dissection. Analysis: descriptive statistics. Results: Response Rate: 108 of 182 participants (59%), representing 20 academic institutions. Case 1: 78% of respondents would screen using CTA (97%), immediately (88%). Most respondents (97%) would initiate treatment, using aspirin (89%) for 3-6 months (46%). Case 2: 73% of respondents would screen using CTA (96%), immediately (88%). The majority of respondents (94%) would initiate treatment, using aspirin (50%) for 3-6 months (35%). Thirty-six percent of respondents would utilize endovascular therapy. In both cases, the majority of respondents would follow-up clinically or radiographically every 1-3 months, respectively. Conclusions: This study highlights consensus in Canadian practice patterns for the workup and management of asymptomatic eTVAI.